Mr Jefferson’s Table: The Culinary Legacy of Monticello - Hess, Karen (Petits Propos Culinaires, 2025)
We print here the text of an address given by Karen Hess to an audience at Monticello in the summer of 2000. It is by way of a progress report on her investigation of the cookery and gardening at Monticello and is expressed with her usual vigour. The text is altered slightly to take account of its passage from the spoken to the written word